Self-reported health, physical activity and socio-economic status of middle-aged and elderly participants in a popular road running race in Switzerland: better off than the general population? (Swiss Medical Weekly, 2012)
INTRODUCTION: In affluent countries habitual physical activity (PA) levels are low while participation of middle-aged people  in road running events is increasing. We compared PA determinants of runners aged 50+ to those of a general population sample of similar age in Switzerland. METHOD: Cross-sectional study comparing 580 road running event participants to 1,067 general population subjects. Binary logistic regression was used to predict group membership and multinomial logistic regression to describe relationships between regular PA levels, health and socio-economic status, adjusted for age, marital status and sex. RESULTS: There was better health status, higher socio-economic position, less obesity and less depression in the runners than in the general population. People in self-reported “poor / very poor” and “good” health categories were less likely than the “excellent/very good” category to engage in vigorous regular PA compared to moderate regular PA. CONCLUSIONS: Our findings confirm the association of PA with better health and higher socio-economic status in people aged 50+ but do not allow conclusions on causality. Further research and managerial effort should be expanded to develop programmes  for the inactive population.   New  and   existing  prevention programmes should be undertaken to increase the awareness of target audiences. Popular road running events should be seen as having important public health potential and should be fostered.